'Know‐Can' gap: gap between knowledge and skills related to childhood diarrhoea and pneumonia among frontline workers in rural Uttar Pradesh, India. Issue 4 (18th January 2020) - Ray Saraswati, Lopamudra; Baker, Margaret; Mishra, Ashutosh; Bhandari, Prince; Rai, Animesh; Mishra, Punit; Chandan, Ambrish; Crockett, Maryanne; Pelly, Lorine; Anthony, John; Shetye, Mrunal; Krotki, Karol; et al.
Abstract: Objectives: In India, frontline workers (FLWs) – public accredited social health activists (ASHAs) and private rural medical providers (RMPs) – are important for early detection and treatment of childhood diarrhoea and pneumonia. This cross‐sectional study aims to measure knowledge and skills, and the gap between the two ('know‐can' gap), regarding assessment of childhood diarrhoea with dehydration and pneumonia among FLWs, and to explore factors associated with them. Methods: We surveyed 473 ASHAs and 447 RMPs in six districts of Uttar Pradesh. We assessed knowledge and skills using face‐to‐face interviews and video vignettes, respectively, about key signs of both conditions. The 'know‐can' gap corresponds to absent skills among FLWs with correct knowledge. We used logistic regression to identify the correlates of knowledge and skills. Results: FLWs' correct knowledge ranged from 23% to 48% for dehydration signs and 27% to 37% for pneumonia signs. Their skills ranged from 3% to 42% for dehydration and 3% to 18% for pneumonia. There was a significant 'know‐can' gap in all the signs, except 'sunken eyes'. Training and supervisory support was associated with better knowledge and skills for diarrhoea with dehydration, but only better knowledge for pneumonia. Conclusions: FLWs are crucial to the Indian health system, and high‐quality FLW services are necessary for continued progress against under‐five deaths. The gap between FLWs' knowledge and skills warrants immediate attention. In particular, our results suggest that knowledge‐focused trainings are insufficient for FLWs to convert knowledge into appropriate assessment skills. Abstract : Objectifs: En Inde, les travailleurs de première ligne (TPL) ‐ activistes de la santé sociale accrédités par le public (ASSAP) et prestataires médicaux ruraux privés (PMRP) ‐ sont importants pour la détection et le traitement précoces de la diarrhée et de la pneumonie infantiles. Cette étude transversale vise à mesurer les connaissances et les compétences, et l'écart entre les deux (écart ''savoir‐pouvoir''), en ce qui concerne l'évaluation de la diarrhée infantile avec déshydratation et la pneumonie chez les TPL et à explorer les facteurs qui leur sont associés. Méthodes: Nous avons mené une enquête sur 473 ASSAP et 447 PMRP dans six districts de l'Uttar Pradesh. Nous avons évalué les connaissances et les compétences à l'aide d'entretiens de face à face et de vignettes vidéo, respectivement, sur les signes clés des deux conditions. L'écart «savoir‐pouvoir» correspond à des compétences absentes parmi les TPL ayant des connaissances correctes. Nous avons utilisé la régression logistique pour identifier les corrélats des connaissances et des compétences. Résultats: Les connaissances correctes des TPL variaient de 23% à 48% pour les signes de déshydratation, 27% à 37% pour les signes de pneumonie. Leurs compétences variaient de 3% à 42% pour la déshydratation et de 3% à 18% pour la pneumonie. Il y avait un écart important dans le «savoir‐pouvoir» pour tous les signes, à l'exception des «yeux enfoncés». La formation et le soutien à la supervision étaient associés à de meilleures connaissances et compétences pour la diarrhée avec déshydratation, mais seulement à de meilleures connaissances pour la pneumonie. Conclusions: Les TPL sont cruciaux pour le système de santé indien, et des services de TPL de haute qualité sont nécessaires pour continuer à lutter contre les décès d'enfants de moins de cinq ans. L'écart entre les connaissances et les compétences des TPL mérite une attention immédiate. En particulier, nos résultats suggèrent que les formations axées sur les connaissances sont insuffisantes pour que les TPL convertissent les connaissances en compétences d'évaluation appropriées.